Numerical competencies of sixth grade students of the Nuestra Señora de Guadalupe municipal educational institution in the township of Botanilla in Pasto - Colombia - Paz, Luis Fernando; Martínez, Juan Carlos (Impacto Científico, 2022)
The purpose of the following investigation is to describe the numerical competences of the 6th grade students of the Municipal Educational Institution Nuestra Señora de Guadalupe in the Corregimiento of Botanilla in the City of Pasto. The research is approached as descriptive with a contemporary transectional field design. The population was made up of 52 students from the institution studied. For data collection, the Evaluate to Advance test built by ICFES is used. Descriptive statistics were used in data analysis and the mean was used as a measure of central tendency, since the test is standardized. The results allow us to conclude that students have low numerical skills, which has a significant impact on their student performance, and prevents them from consolidating mathematical knowledge, therefore, they have difficulty solving problems related to everyday life efficiently and effectively.